Enterprise risk management: evidence from small-medium enterprises / Yap Kiew Heong Angeline and Yap Saw Teng. - Yap, Kiew Heong Angeline; Yap, Saw Teng (Universiti Teknologi MARA Cawangan Selangor, 2016)
This paper aims to investigate the extent to which Malaysian small- and medium-sized enterprises (SMEs) practised enterprise risk management (ERM) framework and their effects on sales performance. The components of ERM examined includes: risk appetite, control environment, assessing the risk management framework and control activities. The paper is based on a questionnaire survey study among 214 SMEs that consist of 77.6% (166) from services related enterprises; and 22.4% (48) of manufacturing related enterprises. The data analysis indicates that 80% of the respondents are clear about the importance of risk management to achieve organizational long term sustainability; the senior management is committed to cultivate good culture and have policies to support ERM. More than 20% of the respondents failed to appoint an independent director to chair risk management committee and to obtain external stakeholders' view when developing risk appetite. Regression analysis also indicates that control environment has a significant and positive impact on sales. Hence, it is important for SMEs to establish a structured system of internal control, to appoint oversight functions and independent assurance providers to manage risks. Risk management is vital in SMEs to reduce exposure to business loss. It is recommended that standards and professional bodies need to develop ERM principles applicable to SMEs. This principle should balance between preferences, requirements and resources within SMEs. This paper contributes to the empirical literatures on the extent of ERM practices and their effects on SMEs' sales in emerging markets.